The general council of the First International 1870-1871 : minutes - Institute of Marxism-Leninism of the Central Committee of the Communist Party of the Soviet Union (IML) (Moscow : Progress Publishers, 1964)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Eerste Internationale (1864-1876).